2008
DOI: 10.1177/1350507608098117
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Work Environment on Entrepreneurial Learning of Small-business Owners

Abstract: Despite the widely acknowledged importance of entrepreneurial learning, research specifically addressing the question of what fosters this process is still in poor supply. In the present study, entrepreneurial learning was conceptualised as a distinct type of workplace learning, emphasising the role of the work environment in performing entrepreneurial tasks by owner/managers. A qualitative study was conducted among a specific sample of 25 small-business owners in an innovative, successful sector in the Nether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 39 publications
1
73
1
Order By: Relevance
“…There is research conducted by Lans (2009), Lans et al (2008ab, 2010 and on entrepreneurship competence in greenhouse horticulture, by Du Chatenier (2009) and Du Chatenier et al (2009,2010) on open innovation in large organizations, and Birru (2016), on export competence in the leather industry, again in small and medium sized companies. Furthermore, the study of Bartram (2005) mentioned above was on the relationship between competence and job performance.…”
Section: Effectivenessmentioning
confidence: 99%
“…There is research conducted by Lans (2009), Lans et al (2008ab, 2010 and on entrepreneurship competence in greenhouse horticulture, by Du Chatenier (2009) and Du Chatenier et al (2009,2010) on open innovation in large organizations, and Birru (2016), on export competence in the leather industry, again in small and medium sized companies. Furthermore, the study of Bartram (2005) mentioned above was on the relationship between competence and job performance.…”
Section: Effectivenessmentioning
confidence: 99%
“…Corporate entrepreneurship training programs could be used to train employees of incumbent companies in such areas as creativity, business planning, and corporate entrepreneurship (Kuratko and Montagno, 1989;Kuratko et al, 2001). This type of action might be especially relevant in the agri-food sector because a number of studies have shown that the entrepreneurial success of companies depends on intraorganizational interactions, support, and guidance (e.g., Kilpatrick and Johns, 2003;Lans et al, 2008).…”
Section: Peoplementioning
confidence: 99%
“…The internationalization of SMEs can be encouraged by initiatives aimed at sustaining contacts with foreign partners (e.g., Wilkinson, 2006). Studies in the agrifood industry have shown that networking with international customers, buyer groups, and other supply-chain partners (e.g., Bertolini and Giovannetti, 2006;Lans et al, 2008;Craviotti, 2012) can foster entrepreneurial undertakings.…”
Section: Networkmentioning
confidence: 99%
“…Through the observation and imitation of other people's employment behavior, employment activities (Ozgen & Baron, 2007), to contact and communicate with other members of the social network, graduate can get the support and guidance of the social network members (Lans, Biemans, Verstegen & Mulder, 2008). The existing study on the graduate employability has not yet established a unified measurement scale (Bao & Liu, 2016), especially lack measurement scale of graduate employability based on social networks.…”
Section: Social Network and Network Learningmentioning
confidence: 99%